The ratio between bryophyte functional groups impacts vascular plants in rich fens. Issue 4 (18th October 2019) - Singh, Patrícia; Těšitel, Jakub; Plesková, Zuzana; Peterka, Tomáš; Hájková, Petra; Dítě, Daniel; Pawlikowski, Paweł; Hájek, Michal
Abstract: Question: Fens have a well‐developed bryophyte layer covering most of the ground. Non‐sphagnaceous bryophytes, especially the group of so‐called brown mosses, prevail over sphagna under alkaline conditions. In sub‐alkaline conditions, rich fens allow the co‐occurrence of both these functional groups, but sphagna are competitively superior over non‐sphagnaceous bryophytes and seedlings of vascular plants, and they are currently expanding in some regions. We test whether the ratio between the two major bryophyte functional groups (bryo‐ratio) accounts for the species composition of vascular plants in fens. Location: Central and Eastern Europe. Methods: Analysis of two existing regional‐ and continental‐scale data sets of the vegetation‐ plot records and measured local factors by Canonical Correspondence Analysis with variation partitioning (community‐level analysis) and Structural Equation Modelling (species‐level analysis). Results: At the community level, the bryo‐ratio accounted significantly for species composition of fen‐specialized vascular plants, more obviously in the regional‐scale data set. At the species level, more fen species (50–67% according to the data set) were significantly directly affected (adjusted p  < 0.05) by the bryo‐ratio than by water pH (14–17%) and by measured water table depth (WTD) in the regional data set (12.5%). In the continental data set, the comparable proportions of species were directly affected by the bryo‐ratio and WTD inferred by soil moisture indicator values (50% vs 58%). Most of the species affected significantly by the bryo‐ratio preferred the fens rich in non‐sphagnaceous bryophytes. They were largely those with a low capability of vegetative reproduction. Conclusions: The group of species preferring brown moss patches includes mostly rare and endangered species with a great need for generative reproduction (e.g., Primula farinosa, Triglochin palustris, Pedicularis palustris, Saxifraga hirculus ). Our findings demonstrate the important role of the bryophyte layer in the structuring of vascular plant communities in fens and highlight urgent conservation needs for brown moss patches. Abstract : Water table depth and pH are generally the main determinants of vascular plant species composition in rich fens. Using two vegetation‐plot datasets, continental and regional, we demonstrate another important, yet neglected, factor, the ratio between covers of non‐sphagnaceous bryophytes and sphagna. Many species specialised to fens, including highly endangered species, preferred fen patches dominated by non‐sphagnaceous bryophytes.